A new perspective and comparative study on demixing and gelation behavior of cellulose acetate, cellulose acetate propionate and cellulose acetate butyrate ternary solutions. Issue 7 (28th July 2017) - Okhovat, Ahmad; Karimi, Mohammad; Zokaee Ashtiani, Farzin
Abstract : Cellulose acetate (CA), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB) were fabricated as membrane via nonsolvent induced phase separation process. N, N‐Dimethylformamide (DMF) and N, N‐Dimethylacetamide (DMAc) as solvents and water as nonsolvent were employed. Ternary phase diagrams for all six ternary systems were constructed using Flory‐Huggins theory. In this way, cloud points as well as Berghman's points were determined. Modulus of polymers steepened in various concentration of solvent/nonsolvent mixtures were measured to find the weight fraction of polymer ( w p ) in which vitrification takes place. W P values for CA, CAP, and CAB were obtained 0.59, 0.67, and 0.74 in presence of DMF while those were 0.69, 0.74, and 0.84 in presence of DMAc; whereas glass transition temperatures ( T g ) for three polymers were determined 180°C, 142°C, and 101°C correspondingly. Pure water flux for CA, CAP, and CAB membrane increased from 75.7 to 83.4 and 290.3 and from 109.6 to 116.1 and 400.3 L/m 2 h bar when DMF and DMAc were used as solvents, respectively. Results revealed that as T g of polymer decreases, the membrane structure vitrifies at higher polymer concentration with more porous structure, bigger pores, higher permeate flux followed by decrease in mechanical strength. POLYM. ENG. SCI., 58:1135–1145, 2018. © 2017 Society of Plastics Engineers